Salivary Thromboxane A2-Binding Proteins from Triatomine Vectors of Chagas Disease Inhibit Platelet-Mediated Neutrophil Extracellular Traps (NETs) Formation and Arterial Thrombosis. - Daniella M Mizurini; Jorgeane S Aslan; Tainá Gomes; Dongying Ma; Ivo M B Francischetti; Robson Q Monteiro (Public Library of Science (PLoS), 2015)
BACKGROUND:The saliva of blood-feeding arthropods contains a notable diversity of molecules that target the hemostatic and immune systems of the host. Dipetalodipin and triplatin are triatomine salivary proteins that exhibit high affinity binding to prostanoids, such as TXA2, thus resulting in potent inhibitory effect on platelet aggregation in vitro. It was recently demonstrated that platelet-derived TXA2 mediates the formation of neutrophil extracellular traps (NETs), a newly recognized link between inflammation and thrombosis that promote thrombus growth and stability. METHODOLOGY/PRINCIPAL FINDINGS:This study evaluated the ability of dipetalodipin and triplatin to block NETs formation in vitro. We also investigated the in vivo antithrombotic activity of TXA2 binding proteins by employing two murine models of experimental thrombosis. Remarkably, we observed that both inhibitors abolished the platelet-mediated formation of NETs in vitro. Dipetalodipin and triplatin significantly increased carotid artery occlusion time in a FeCl3-induced injury model. Treatment with TXA2-binding proteins also protected mice from lethal pulmonary thromboembolism evoked by the intravenous injection of collagen and epinephrine. Effective antithrombotic doses of dipetalodipin and triplatin did not increase blood loss, which was estimated using the tail transection method. CONCLUSIONS/SIGNIFICANCE:Salivary TXA2-binding proteins, dipetalodipin and triplatin, are capable to prevent platelet-mediated NETs formation in vitro. This ability may contribute to the antithrombotic effects in vivo. Notably, both molecules inhibit arterial thrombosis without promoting excessive bleeding. Our results provide new insight into the antihemostatic effects of TXA2-binding proteins and may have important significance in elucidating the mechanisms of saliva to avoid host's hemostatic responses and innate immune system.